Dinamika Pemekaran Daerah Di Kepulauan (Studi Penataan Pemekaran Daerah di Kabupaten Lingga Tahun 2015-2025) - Bismar Arianto; Suradji Suradji; Oksep Adhayanto; Imam Yudhi Prastya (Jurnal Selat, 2015)
Since 1999 until 2015, Riau Archipelago Province was a regency. Riau Archipelago had passed development process for six times. In 1999, Karimun Regency, Natuna Regency and Batam City were formed. In 2001, the administrative city of Tanjung Pinang was formed. In 2003, Lingga Regency was formed, and In 2008 Anambas Archipelago Regency was legalized. Until this time, the dynamic of development in Riau Archipelago Province is still powerful. The fact there are five of seven Regencies / cities are in effort to be developed. This dynamic of development also happened in Lingga Regency, eventhought with the smallest Regional Fund Budget in Riau Archipelago Province. the purpose of this study is to explain the efficient estimation and time for new autonomy region increament in Lingga Regency. The parameter of region systemation which is used in this study is based on outonomy region systemation in big design of region systemation in indonesia of 2010-2025 which considered the geography dimension, demography dimension and system dimension. this study concludes based on the dimension of geography, economy, financial system, public administration system, and regional government management system, Natuna Regency is able for one new autonomy region increment. however, based on dimension of demography, security and defence system, and politic and culture social system, Lingga Regency is not recommended for new autonomy Region increment. totally, maximum amount estimation of new autonomy region increment in Lingga until 2025 is only one new autonomy region. The efficient schedule for its development process is in 2019-2021. Key words : Region Development, Territory Systemation and New Autonomy Region